Francisco Suárez y las matemáticas. Notas sobre su carácter científico según las Disputaciones Metafísicas I - Felipe Mendoza, José María (Pontificia Universidad Católica del Perú. Fondo Editorial, 2021)
El presente trabajo propone una introducción a la doctrina de la ciencia matemática de Francisco Suárez según sus Disputationes Metafisicas I. El contexto de la investigación aborda la noción de objeto adecuado, una teoría de la abstracción y el orden de las ciencias especulativas en general. Por ello, para mejor comprender las ciencias matemáticas, es necesario observar su relación con la metafísica, delimitando no solo su fundamento, sino también su horizonte especulativo.

“Francisco Suarez and Mathematics. Remarks on its Scientific Character according to Disputationes Metaphysicae I”. The present work proposes a brief introduction to the mathematical doctrine of Francisco Suarez according to his Disputationes Metaphysicae I. The context of his researching deals with the notion of obiectum aedecuatum, a theory of abstraction and the order of sciences in general terms. Therefore, in order to better understanding the mathematical sciences, it’s necessary to observe its relationship with metaphysics and define the ground and the limits of mathematical philosophy.
Francisco Suarez and Mathematics. Remarks on its Scientific Character according to Disputationes Metaphysicae I
Keywords: Francisco Suárez; metafísica; matemática; Objeto adecuado; Abstracción; https://purl.org/pe-repo/ocde/ford#6.03.01